NEWMAN ERROR ANALYSIS (NEA): DETECTION OF STUDENT LEARNING BARRIERS IN PPKM IN MATHEMATICS SUBJECTS - Sutama Sutama; Yuni Putri Indriyani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
The research aims to analyze students' mistakes in solving straight-line equations and then find the learning barriers experienced during distance learning conducted in the 8th grade of a superior private junior high school in Surakarta City. The research uses qualitative descriptive design with assistive instruments in the form of three straight-line equations material test questions and interview guidelines. Triangulation used is a triangulation method and analysis data is done with the stages of data collection, data reduction, data categorization, presentation and withdrawal of conclusions. Referring to the Newman Error Analysis theory, it is identified that all five types of errors are made by students in solving straight-line equations. The five types of errors are reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. Student errors that appear to indicate obstacles in learning. The rights that arise are the ownership of mobile phones and unstable internet networks, minimal learning supervision, and the availability of fewer learning resources. The results of this study can be used as a basis for developing a learning medium that can be used and supporting online teaching.